Analysis of Differences in Graph Interpretation Understanding of Grade X Students of Madrasah Aliyah Negeri (MAN) 1 Malang on Kinematics Topic Based on Gender - Nora Anggraini; Muhammad Reyza Arief Taqwa; Chusnana Insjaf Yogihati; Grace Djan (Tinta Emas Publisher, 2024)
This study aims to analyze the conception profile of MAN 1 Malang students on the subject matter of kinematics based on gender using multiple choice tests. The type of research used is quantitative descriptive research. This research was conducted on 94 students (47 male and 47 female students) of MAN 1 Malang. Quantitative data was obtained from the score of correct answers from students when answering questions. The method used was survey method. After the validation test and reliability test, there were 20 questions categorized as valid and could be used for research. The questions that passed the test were then given to students to do in the form of a written test. The results showed that students' understanding of the concept of kinematics was categorized as very low. This is due to the average student concept understanding score of 24.04. Based on the data analysis that has been done, it is concluded that there is no difference in concept understanding between male students and female students.